Construction and practice of specialist caredemonstration ward based on "one quality nursing care plan for one syndrome" ("一证一品"专科护理示范病房建设项目应用思路及实践探索) - LI Suqian (李苏茜); TANG Ling (唐玲); LI Ye (李野) (Association of Integrative Nursing, 2021)
In order to improve the clinical nursing quality of Traditional Chinese Medicine(TCM) Hospitals in Beijing, highlight the characteristics and advantages of TCM nursing and promote the inheritance and innovation of TCM, The project of construction and practice of specialist care demonstration ward based on "one quality nursing care plan for one syndrome" had been carried out by Beijing Office of TCM Nursing Competence Improvement Project under the guidance of Beijing Administration of TCM. This paper summarized the construction and practice experience of the project, and provided reference for the further research on the construction of high-quality care demonstration ward. (为了促进北京市中医医疗机构临床护理工作的发展, 突出中医护理的特色与优势, 使中医护理在继承中创新发展, 在北京市中医管理局的指导下, 北京市中医护理能力提升工程办公室于2017年10月开展"一证一品"专科护理示范病房建设项目。本文对该项目建设的实施方案以及成果进行总结, 为进一步深入开展优质护理示范病房工作提供参考。)